The relationship between nursıng students\' humor styles and perceived care behaviors - Burcu Oflaz; Gülcan Kendirkıran (Golestan University of Medical Sciences, 2023)
Background: Humor creates intimacy between the patient and the nurse, develops a feeling of trust, and positively affects care quality. This study aimed to determine nursing students' humor styles and care behaviors and evaluate the relationship between their humor styles and perceived care behaviors. Methods: This was a cross-sectional and analytical research. The sample comprised 124 second-, third-, and fourth-year nursing students at a university located in Istanbul between December 2019 and December 2020. The data collection tools were a Personal Information Form, Humor Styles Scale, and Care Assessment Questionnaire. Frequency tables, descriptive statistics, independent samples t-test, analysis of variance, Mann-Whitney-U test, Kruskal-Wallis H test, Bonferroni correction, and Spearman correlation were employed to analyze the data.   Results: It was determined that 86.3% of the nursing students were female, 97.6% were single, their mean age was 20.80±1.94 years, and 49.2% of the students were second-year students. The total mean score of the students on the Care Assessment Questionnaire was 6.38±0.51. A positive humor style was significantly related to the subscales of the Care Assessment Questionnaire (P<0.05). Conclusions: There was a significant relationship between nursing students' humor styles and perceived care behaviors. The positive humor style had a positive effect on the caring behavior.